1994
DOI: 10.1128/jcm.32.1.176-186.1994
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis and vaginal microorganisms in idiopathic premature labor and association with pregnancy outcome

Abstract: The vaginal microflora of 49 women in idiopathic preterm labor was compared with that of 38 term controls to determine whether the presence of bacterial vaginosis (BV) and/or specific microorganisms would influence the rate of preterm delivery. Demographic factors, pregnancy outcome, and reproductive history were also studied. BV, as defined by the presence of clue cells in a vaginal wet mount and characteristic microbial findings in a stained vaginal smear and vaginal culture, was more common in women with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
92
2
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(99 citation statements)
references
References 65 publications
(67 reference statements)
4
92
2
1
Order By: Relevance
“…In our study, both culture and CDH indicated that staphylococci and streptococci may stimulate increased cytokine secretion (IL-1 and IL-8) in asymptomatic healthy women (Tables 5 & 9). B. ureolyt- The vaginal presence of these two strains has been reported to be associated with preterm delivery, amniotic fluid infection or elevated IL-6 levels in the amniotic fluid (17,62). It appears that microbial patterns or single bacterial species, including several strict anaerobic Gramnegative bacteria, need to be related to the grade of clinical and laboratory inflammatory signs in order to clarify whether there are distinct entities of abnormal vaginal microbiota leading to somewhat different host responses, especially respecting intrauterine subclinical infection in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, both culture and CDH indicated that staphylococci and streptococci may stimulate increased cytokine secretion (IL-1 and IL-8) in asymptomatic healthy women (Tables 5 & 9). B. ureolyt- The vaginal presence of these two strains has been reported to be associated with preterm delivery, amniotic fluid infection or elevated IL-6 levels in the amniotic fluid (17,62). It appears that microbial patterns or single bacterial species, including several strict anaerobic Gramnegative bacteria, need to be related to the grade of clinical and laboratory inflammatory signs in order to clarify whether there are distinct entities of abnormal vaginal microbiota leading to somewhat different host responses, especially respecting intrauterine subclinical infection in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Both periodontal disease and bacterial vaginosis have been linked to adverse pregnancy outcomes such as pre-term birth and low birth weight in numerous studies (Holst et al 1994, Hillier et al 1995, Offenbacher et al 1996, Jeffcoat et al 2001, Goepfert et al 2004, De Seta et al 2005, Dortbudak et al 2005), yet the pathological mechanisms through which they may induce an immune response resulting in pre-term birth remain unclear. While not identical, microbiological similarities between the oral and vaginal environments in the presence of periodontal disease and bacterial vaginosis, respectively, may indicate a common pathophysiology, such as a deficient host response to infection (Genco 1992, Cauci 2004).…”
mentioning
confidence: 99%
“…It is possible that BV is a marker of similar organisms in the vagina and in the uterine cavity (6). Only one case-control study has been previously published investigating a Swedish pregnant population regarding BV and PTB (7).…”
mentioning
confidence: 99%